(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Based on our experience, it was found that seller is a class III drug with a 20% toxicity. The drug has an irritating effect on the skin and eyemucosa. The daily dose 0,72mg/kg/ day. Has no carcinogenic, mutagenic, embryotoxicaction. As a result of the research, the insecticide isdetermined by the amount of atmospheric air and jobs allowed, maximum permissible levels in food, and possible levels in food, and possiblesoil contamination